On the partial differential equations with non-constant coefficients and convolution method. - Kilicman, Adem; Eltayeb, Hassan (2010)
In this study we consider the linear second order partial differential equations with non-homogenous forcing term and having singular variable data. In the special case we solve the one dimensional wave equation by using the double integral transform.